Kesultanan Jambi dalam Jaringan Perdagangan Antar Bangsa (1480-1834) - Arif Rahim (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This paper discusses the Jambi kingdom and its existence as a country located on the international trade route. This is interesting to study because the period of its existence coincided with the golden age of trade between nations which involved emporium countries that were located along the trade route from China in the east to the Mediterranean in the western tip. This period is said by historians to be the prosperous era of the Asian emporium. By using a multi-dimensional approach and supported by the application of historical methods that refer to scientific historical research procedures, the results of this study are expected to provide an explanation of the main problems posed and thus contribute to the development of science, especially about Jambi's local history. In addition, it can be used as material for consideration by related institutions in order to preserve historical and cultural values and for regional development. The results of the study show that the Jambi region has been involved in international trade networks since the beginning of the century AD, but its nature has experienced ups and downs. From the 3rd century to the 7th century Jambi's involvement was evident in the existence of the Koying, Tupo, Kantoli and Malay kingdoms. From the 7th century to the 11th century that role declined because the Malay kingdom was controlled by Srivijaya, which was centered in Palembang. When Srivijaya weakened in the 11th century, Malays broke away and re-emerged as an important trading port in the archipelago. Entering the 12th century, this role has declined again due to competition from other trading ports located on the east coast of North Sumatra, as well as direct trade to the interior. The Jambi kingdom was re-established at the end of the 15th century, reaching its peak in the 17th century when pepper became an important commodity in international trade. As a large pepper producing country, Jambi emerged as an important trading port which was visited by both foreign and Nusantara traders. But since the end of the 17th century, Jambi has been in decline. The cause was Jambi's defeat of Johor in repeated wars between 1667 and 1673. Other reasons were the internal conflict of the kingdom, and the Dutch intervention in the affairs of the royal government, as well as the falling price of pepper on the international market. The decline in the price of pepper led to a decrease in the income of the kingdom and the community, thus causing the reluctance of traders to come to Jambi Port. In the 19th century the port of Jambi was no longer visited by maritime merchants of the archipelago.